International practice of allergen products standardization - L. V. Nevskaya; E. I. Lavrenchik; M. Yu. Zhdanova; O. V. Fadeykina; V. K. Kapitanova (Биопрепараты: Профилактика, диагностика, лечение)
The article demonstrates that safe and efficacious use of allergen products for detection and treatment of allergic diseases relies on standardization and quality control methods. The article summarises various approaches to allergen products standardization that are used in the United States, the European Union and the Russian Federation. Development of requirements for allergen products of natural origin must take account of the heterogeneity of raw materials used in their production, since native allergen extracts are complex protein-polysaccharide mixtures consisting of allergenic (primary and secondary) and non-allergenic components. Standardization of methods used for evaluation of allergen products potency is performed using reference standards. To date, there exist several approaches to allergens standardization. The United States introduced a system of national reference standards whose biological activity is determined by one technique (IntraDermal Dilution for 50 mm sum of Erythema determines bioequivalent Allergy Units - ID50EAL). In Europe each manufacturer establishes their own in-house reference standards (IHRS) and assigns them with units of activity. Products manufactured in the Russian Federation are standardized in protein nitrogen units (PNU).